2017
DOI: 10.3390/ijms18112424
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRα Regulated by miR-34a and FoxO1 Promotes Adipogenesis in Porcine Intramuscular Preadipocytes through Erk Signaling Pathway

Abstract: Suitable intramuscular fat (IMF) content improves porcine meat quality. The vital genes regulating IMF deposition are necessary for the selection and breeding of an IMF trait. However, the effect and mechanism of PDGFRα on IMF deposition are still unclear. Here, PDGFRα is moderately expressed in porcine longissimus dorsi muscle (LD), whereas it highly expressed in white adipose tissue (WAT). Moreover, PDGFRα-positive cells were located in the gaps of LD fibers which there were IMF adipocytes. Compared with 180… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 39 publications
2
27
1
1
Order By: Relevance
“…5e, f). Our results are consistent with one previous study [53], but are inconsistent with a recent report that overexpression of miR-34a increases lipid deposition in mouse liver and HepG2 cells [54]. The discrepancy may be due to differences between species or cell type.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…5e, f). Our results are consistent with one previous study [53], but are inconsistent with a recent report that overexpression of miR-34a increases lipid deposition in mouse liver and HepG2 cells [54]. The discrepancy may be due to differences between species or cell type.…”
Section: Discussioncontrasting
confidence: 65%
“…Visible connective tissue was removed, and the remaining tissue was finely minced. Following the protocol described in a previous study [53], preadipocytes were isolated using differential rate adherence by subjecting the tissues to digestion for 2 h with 0.1% type II collagenase. The digested sample was filtered aseptically through a 200 μm nylon mesh filter to isolate cells.…”
Section: Dual Luciferase Reporter Assaymentioning
confidence: 99%
“…Guo et al [ 15 ] suggested that up-regulated miR-145 expression inhibited porcine preadipocyte differentiation by negatively regulating insulin receptor substrate 1 ( IRS1 ). Sun et al [ 16 ] demonstrated that miR-34a enhanced adipogenesis in porcine intramuscular preadipocytes through the extracellular regulated MAP kinase (Erk) signaling pathway. Previously, miR-125a-5p was shown to mediate adipogenesis in 3T3-L1 cells and porcine preadipocytes [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus PDGFRA is a marker of intramuscular adipocyte progenitors in beef cattle (Huang et al, 2012a;Miao et al, 2016). In pigs, PDGFRA þ cells are located in the gaps of myofibers in longissimus dorsi muscle, and more PDGFRA þ cells are detected in longissimus dorsi muscle of fat-type pigs compared with that of lean-type pigs at 180 days of age (Sun et al, 2017), albeit no difference was observed in the abundance of PDGFRA þ cells or PDGFRA expression between longissimus thoracis (with higher IMF contents) and semitendinosus muscle (with lower IMF) in 180-day-old pigs (Chen et al, 2019).…”
Section: Molecular Markers and Heterogeneity Of Fibro-adipogenic Progmentioning
confidence: 98%
“…The origins of muscular fibro-adipogenic progenitors The muscle stromal vascular fractions (SVFs), containing a mixture of mesenchymal stem/stromal cells (MSCs), fibroblasts, immune cells and endothelial cells (Perruchot et al, 2013;Wosczyna et al, 2019), have been widely used for in vitro studies of intramuscular adipogenesis (Zhou et al, 2010;Jiang et al, 2013;Zhang et al, 2014;Sun et al, 2017 andChen et al, 2019); however, the origins of intramuscular adipocytes had remained largely undefined until fairly recently.…”
Section: Molecular Markers and Heterogeneity Of Fibro-adipogenic Progmentioning
confidence: 99%